Strategi Pemasaran dan Branding dalam Wirausaha Kopi Botol - Imam Hasani; Hartin Kurniawati (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2024)
This research analyzes marketing and branding strategies in bottled coffee entrepreneurship, with a case study of Hammam Thoriq Majid's Bolo Coffee business. The research objectives are to identify target markets, analyze competitive positions, develop differentiation strategies, evaluate marketing channels, design branding strategies, and provide practical recommendations for Kopi Bolo entrepreneurs. The research method used is qualitative, with data collection through literature study, interviews and observation. The research results show that effective marketing and branding strategies include understanding the target market, utilizing social media, managing relevant content, strong brand identity, measuring campaign effectiveness, and commitment to quality and innovation. Competitor analysis and consumer interest surveys also provide valuable insights for designing strategies relevant to market preferences. This research provides an academic contribution in developing marketing and branding concepts for bottled coffee entrepreneurs, as well as a practical guide for Kopi Bolo and similar businesses in facing dynamic competition.